TEOLOGI SHARE DALAM DAKWAH ISLAM - Irfan Afandi (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2024)
This article reviews the significant theological impact of sharing da'wah content on social media. Even if someone is passionate about sharing religious content, an important question arises about their ability to actually do so? This research is based on the understanding of Qs. Ash Shaaf: 2-3 which emphasizes the conviction of Allah SWT for people who say something without being able to do it. This research is a text research. The data used are the text of the Qur'an, hadith and the text of the book of tafsir. The data collected was analyzed in a qualitative descriptive manner with an inductive approach, aiming to compile and conclude a pattern of understanding regarding the method of interpreting the verses of the Qur'an. The data is validated by triangulation of the source in the text. Then, the data is analyzed using content analysis where the researcher explores and analyzes words, phrases, themes, or concepts in a text or series of texts.The behavior of sharing relegated content has three behavioral tendencies, the first is sharing with the intention of understanding, doing, and spreading Islamic teachings. Second, share to convey the truth as knowledge, even though they have not been able to do it themselves. Third, for commercial purposes, only for likes, advertisements, and money without paying attention to the content of the teachings being spread. consequently, if the intention to share to understand, practice, and spread the teachings of Islam, is considered the main behavior that is mandatory for Muslims. If you want to convey the knowledge of the truth even though you have not been able to do it, like an ustadz who spreads hadith about Hajj but has never performed Hajj, this is a commendable behavior. If sharing da'wah content is only for business purposes, regardless of the content or applying Islamic teachings that are spread, it will receive criticism from Allah SWT as in QS. Al-Shaaf: 2-3.